Development of computer aided design of rectangular reinforced concrete column by using Visual Basic 6.0 / Mohd Akmal Salleh - Salleh, Mohd Akmal (2007)
Column is one of the vital parts in construction. It needs to be design precisely with accurate calculation in order to avoid any failure in construction. There are 2 main types of column that are Braced Column and Unbraced Column. Each of these 2 columns has its own types of classification. In order to design these column its types of classification has to be taken in consideration during calculation. However the most common column used is Braced column because buildings usually have shear walls. As the calculations in designing columns are tedious, developing a simple but yet affective software using Visual Basic is appropriate. The software will save time in designing column hence allow us to recheck our calculation easily. However, aside from calculation process of column design, the detailing and its reinforcement arrangement are also important to be determined. Finally, all the design process still refers to the design techniques of BS 8110 Part 1, BS 8110 Part 2 and BS 8110 Part 3.